Student with hearing impairment in third level education: Support system applied at universities in Slovakia - Sender, Barbora; Polackova, Vladimira (Sensos-e, 2024)
In recent decades, the ideal of inclusive education has become a priority idea of educational systems all over the world. The presented article deals with the current state of inclusion at universities in Slovakia. It describes the situation at the selected university in terms of support and help provided for students with specific needs. It represents a less discussed topic focused on the social and educational inclusion of students with hearing impairment. The aim of the contribution is to draw attention to the inclusion of students with hearing impairments in higher education, to offer theoretical definition and an analysis of the specifics of communication of the hearing-impaired students, as well as to monitor the impact of the impairment on education. A short description about Erasmus + project focused on inclusion within third level education institution of three joint countries is also part of the presented paper.